2008
DOI: 10.1029/2008gl033641
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented evidence for deep convection hydrating the tropical stratosphere

Abstract: [1] We report on in situ and remote sensing measurements of ice particles in the tropical stratosphere found during the Geophysica campaigns TROCCINOX and SCOUT-O3. We show that the deep convective systems penetrated the stratosphere and deposited ice particles at altitudes reaching 420 K potential temperature. These convective events had a hydrating effect on the lower tropical stratosphere due to evaporation of the ice particles. In contrast, there were no signs of convectively induced dehydration in the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
252
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(277 citation statements)
references
References 22 publications
(28 reference statements)
23
252
0
2
Order By: Relevance
“…Sherwood and Dessler (2000) postulated that dehydration might be primarily due to deep convective overshooting. However, experiments showed that overshooting convection hydrates rather than dehydrates the tropical lower stratosphere (e.g., Corti et al, 2008). Lagrangian trajectory calculations driven by synoptic-scale temperature and wind fileds from reanalysis data (Fueglistaler et al, 2005;Schoeberl and Dessler, 2011) can reproduce the entry of water vapor into the stratosphere well, validating the idea of Holton and Gettleman (2001).…”
Section: Introductionsupporting
confidence: 56%
“…Sherwood and Dessler (2000) postulated that dehydration might be primarily due to deep convective overshooting. However, experiments showed that overshooting convection hydrates rather than dehydrates the tropical lower stratosphere (e.g., Corti et al, 2008). Lagrangian trajectory calculations driven by synoptic-scale temperature and wind fileds from reanalysis data (Fueglistaler et al, 2005;Schoeberl and Dessler, 2011) can reproduce the entry of water vapor into the stratosphere well, validating the idea of Holton and Gettleman (2001).…”
Section: Introductionsupporting
confidence: 56%
“…A considerable amount of observational evidence for cross-tropopause mass transport through convective overshooting has been made available by recent field campaigns in South America, Australia and Africa, revealing penetration of tropospheric air and ice crystals up to 19-20 km over land convective systems (Nielsen et al, 2007;Corti et al, 2008;Khaykin et al, 2009;de Reus et al, 2009;. Such convective updrafts of adiabatically cooled air and ice crystals across the tropopause are well captured by mesoscale cloud resolving models (Chaboureau et al, 2007;Jensen et al, 2007;Grosvenor et al, 2007;Chemel et al, 2009;Liu et al, 2010), but, because of their non-hydrostatic nature, they are missed by global meteorological and climate models.…”
Section: S M Khaykin Et Al: Impact Of Land Convection On Temperatumentioning
confidence: 99%
“…These difficulties arise from temperature biases, the representation of sub-grid scale phenomena such as convective moistening (Zipser et al, 2006;Schiller et al, 2009;Corti et al, 2008;Tzella and LeGras, 2011) and gravity wave cooling (Jensen and Pfister, 2004). In Schoeberl and Dessler (2011) (hereafter SD2011), we used a Lagrangian forward domain-filling model to simulate water vapor in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%